ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT SUKU BUNGA DEPOSITO BERJANGKA BANK UMUM NASIONAL YANG TERDAFTAR DI BEI PERIODE 2010-2012 - Widi Mularsih, 07.05.52.0085; Badjuri, Achmad (Students Journal of Accounting and Banking, 2014)
The purpose of this research is to emperically study effect of inflation, CAR, LDR, and ROA effect on the rate time deposits. The population of this research is all the financial data of listed companies on the Stock Exchange during 2010-2012. The sampling method used in this study is purposive sampling method. The sample used in this study were 27 banking companies listed on the Stock Exchange in the period 2010-2012. The data used are secondary data from ICMD. The analysis technique used is multiple linear regression. Based on the calculation results of the t test was performed, negative effect on the inflation rate time deposits and ROA negatively affect the interest rates on time deposits. While the CAR and LDR does not affect the interest rates on time deposits.Keywords: Inflation, CAR, LDR, ROA, interest rates on time deposits